Investigation of phenyl azide photochemistry by conventional and time-resolved spectroscopy. Elucidation of intermediates and reaction mechanisms - Elisa Leyva; Matthew S. Platz; Edgar Moctezuma (Journal of Photochemistry and Photobiology, 2022)
Early studies of the photochemistry of parent phenyl azide concerned the products obtained under specific experimental conditions. Depending on the products, various mechanisms and intermediates were proposed. Later work involving conventional spectroscopic studies in low temperature matrices allowed the direct detection and identification of several intermediates. Electron Spin Resonance spectroscopy allowed the determination of a ground triplet phenyl nitrene and IR spectroscopy allowed the direct observation of ketenimine and bicyclic azirine. However, low temperature spectroscopy studies gave contradictory results with the formation of secondary photochemical intermediates and products. Recent studies using-time resolved spectroscopy allowed the direct observation of singlet phenyl nitrene. Furthermore, modern computational tools helped to corroborate experimental spectra of intermediates and to determine electronic structure of other possible intermediates, relative energies and mechanistic pathways. A unified picture of the photochemistry of phenyl azide has emerged from experimental, spectroscopic and theoretical studies. In this review, the results presented in each methodology are discussed.